Electrical Microneedles for Wound Treatment - Yu Wang; Lijun Cai; Lu Fan; Li Wang; Feika Bian; Weijian Sun; Yuanjin Zhao (Advanced Science)
Abstract Electrical stimulation has been hotpot research and provoked extensive interest in a broad application such as wound closure, tissue injury repair, and nerve engineering. In particular, immense efforts have been dedicated to developing electrical microneedles, which demonstrate unique features in terms of controllable drug release, real‐time monitoring, and therapy, thus greatly accelerating the process of wound healing. Here, a review of state‐of‐art research concerning electrical microneedles applied for wound treatment is presented. After a comprehensive analysis of the mechanisms of electrical stimulation on wound healing, the derived three types of electrical microneedles are clarified and summarized. Further, their applications in wound healing are highlighted. Finally, current perspectives and directions for the development of future electrical microneedles in improving wound healing are addressed.